2020
DOI: 10.1088/1555-6611/ab8dc9
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a novel Green’s function-based method for laser and matter thermal interaction

Abstract: The thermal interaction of lasers with matter is studied in this work. Using the Green's function approach, equations governing this interaction are solved semi-analytically. Real conditions, such as the temperature dependence of thermal coefficients, and the surface radiation of matter, were taken into account when solving these equations. A computational code was written in the C programming language to simulate the problem. The proposed method decreases both calculation and simulation times considerably. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In [31] the interaction of laser and matter is simulated by means of a semi-analytical model obtained combining a Green's function analytical method with a finite difference numerical method. In this study the temperature distribution in the matter was calculated.…”
Section: Introductionmentioning
confidence: 99%
“…In [31] the interaction of laser and matter is simulated by means of a semi-analytical model obtained combining a Green's function analytical method with a finite difference numerical method. In this study the temperature distribution in the matter was calculated.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the anisotropic electrical response of a shale core has been monitored under the ultraviolet laser irradiation [14]. The destruction of drilling rock was also performed using a KrF laser beam [15][16][17][18]. It was concluded that the characteristic of shales can be represented with laserinduced voltage (LIV).…”
Section: Introductionmentioning
confidence: 99%